ANTESEDEN LOYALITAS KONSUMEN PADA BIRO PERJALANAN WISATA DI JAKARTA - Rudyanto Rudyanto (Media Riset Bisnis & Manajemen, 2013)
This study aims to assess the effect of antecedent of relational quality such as satisfaction, trust, and commitment in consumers' loyalty Travel Bureau in Jakarta. This study used 252 consumer respondents Travel Bureau in Jakarta. Research variables have good reliability and validity, the concept model and hypotheses were tested with LISREL 8.80. The results showed satisfaction has a positive influence on confidence; Satisfaction has a positive influence on commitment; Trust had a positive effect on commitment, and confidence positive effect on loyalty; Loyalty consumers will be well established by the quality of the relational ties are good also (Satisfaction, Trust and Commitment). Theoretical implications of research that can be obtained that consumer loyalty are well formed if guided by satisfaction, trust, and commitment to the travel bureau. Travel Bureau constantly has to develop the ability to enhance the relational ties to consumers in order to create sustainable loyalty.